Pengaruh Model Pembelajaran Problem Based Learning (PBL) Menggunakan Media Kahoot terhadap Pemahaman Siswa pada Mata Pelajaran Pendidikan Agama Islam Kelas XI SMK Negeri 5 Bone - Surianti Surianti; Andi Hajar; A. Suharman (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study aims to determine the Effect of Problem Based Learning (PBL) Learning Model Using Kahoot Media on Student Understanding in Islamic Religious Education Subjects of Class XI SMK Negeri 5 Bone. The background of this study is the lack of conventional approaches that are predominantly used by teachers in schools, as well as the selection of learning models and media that are less interesting so that it is difficult for students to understand the material and hinder their understanding in the learning process. Problem Based Learning (PBL) and Kahoot are learning models and media by designing problem-centered learning and utilizing technology by using educational website-based media designed in the form of collaborative games to stimulate students' understanding and interest in learning. The method used in this study is a quantitative method with a pre-experimental research type that uses a one-group pretest-posttest design. The sample of this study was class XI majoring in TKJ SMK Negeri 5 Bone, Based on the results of data analysis, the average value of Pre-test was 44.11 and Post-test 82.05. Analysis of t-test data obtained t count 14.339> t table 1.694. The results of this study indicate that there is an influence of the Problem Based Learning (PBL) Learning Model Using Kahoot Media on Students' Understanding of Islamic Religious Education Subjects in class XI of SMK Negeri 5 Bone”. Academic Year 2024/2025.